2016
DOI: 10.1364/ol.41.000305
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the polarization behavior of quantum cascade lasers by Stokes parameters

Abstract: We experimentally investigate the full polarization behavior of mid-infrared emitting quantum cascade lasers (QCLs) in terms of measuring the complete Stokes parameters, instead of only projecting them on a linear polarization basis. We demonstrate that besides the pre-dominant linear TM polarization of the emitted light as governed by the selection rules of the intersubband transition, small non-TM contributions, e.g., circularly polarized light, are present reflecting the birefringent behavior of the semicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…QCLs predominantly emit transverse magnetic (TM) polarized light with an electric field vector perpendicular to the plane of the quantum wells, which is characteristic of their fundamental structure. However, QCL emissions have also been reported to contain a small circular component and other orthogonal polarization components that could be attributed to the induced birefringence of the QCL waveguides used for directing the emitted light . We experimentally verify the polarization characteristics of each laser in an example 4-laser QC system, with each laser tuned to the center wavenumber of its gain curve as shown in Figure A.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…QCLs predominantly emit transverse magnetic (TM) polarized light with an electric field vector perpendicular to the plane of the quantum wells, which is characteristic of their fundamental structure. However, QCL emissions have also been reported to contain a small circular component and other orthogonal polarization components that could be attributed to the induced birefringence of the QCL waveguides used for directing the emitted light . We experimentally verify the polarization characteristics of each laser in an example 4-laser QC system, with each laser tuned to the center wavenumber of its gain curve as shown in Figure A.…”
Section: Resultsmentioning
confidence: 98%
“…However, QCL emissions have also been reported to contain a small circular component and other orthogonal polarization components that could be attributed to the induced birefringence of the QCL waveguides used for directing the emitted light. 31 We experimentally verify the polarization characteristics of each laser in an example 4-laser QC system, with each laser tuned to the center wavenumber of its gain curve as shown in Figure 3A. A polarizer is placed in front of the QCL such that the fast axis of the polarizer is aligned with the QCL's polarization axis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that differently polarized light is present in the beam of quantum cascade lasers with symmetric waveguides (Pruszyńska- Karbownik et al 2015). A study of another research group showed that in a QCL beam there is a non-negligible amount of circularly polarized light (Janassek et al 2016). Recently, we have shown that the TE-like polarized light may come from unevennesses of the rear laser mirror (Pruszyńska- Karbownik and Łaszcz 2018).…”
Section: Introductionmentioning
confidence: 98%
“…In intersubband transitions, only the component of the electric field normal to the quantum wells can optically couple to quantum oscillators hence meaning that the light emitted by QCLs is TM polarized because of the selection rule associated to the enveloped functions [3]. Despite that, some experiments have shown that this selection rule is not always verified in quantum well infrared photodetectors (QWIPs) [4] and QCLs [5] wherein the remaining TE component can be as strong as a few percent of the TM component. When applying conventional optical feedback to a QCL, the back-reflected wave is mainly TM polarized and this triggers non-linear dynamics in the TM mode of the laser.…”
Section: Introductionmentioning
confidence: 99%